2015
DOI: 10.3174/ajnr.a4311
|View full text |Cite
|
Sign up to set email alerts
|

Mean Diffusional Kurtosis in Patients with Glioma: Initial Results with a Fast Imaging Method in a Clinical Setting

Abstract: BACKGROUND AND PURPOSE:Diffusional kurtosis imaging is an MR imaging technique that provides microstructural information in biologic systems. Its application in clinical studies, however, is hampered by long acquisition and postprocessing times. We evaluated a new and fast (2 minutes 46 seconds) diffusional kurtosis imaging method with regard to glioma grading, compared it with conventional diffusional kurtosis imaging, and compared the diagnostic accuracy of fast mean kurtosis (MKЈ) to that of the widely used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 22 publications
5
58
0
Order By: Relevance
“…For example, diffusional kurtosis imaging (DKI) (Jensen et al, 2005) probes heterogeneity in terms of a normalized variance metric called the diffusional kurtosis. The kurtosis has been used to differentiate low and high grade gliomas, where increased heterogeneity was related to higher malignancy (Raab et al, 2010; Tietze et al, 2015; Van Cauter et al, 2012). However, the interpretation of diffusional variance parameters, such as the mean kurtosis, is challenging, and its link to relevant features of the underlying microstructure remain unclear (Jespersen et al, 2010; Le Bihan, 2013; Maier et al, 2010; Tietze et al, 2015; Wu and Cheung, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, diffusional kurtosis imaging (DKI) (Jensen et al, 2005) probes heterogeneity in terms of a normalized variance metric called the diffusional kurtosis. The kurtosis has been used to differentiate low and high grade gliomas, where increased heterogeneity was related to higher malignancy (Raab et al, 2010; Tietze et al, 2015; Van Cauter et al, 2012). However, the interpretation of diffusional variance parameters, such as the mean kurtosis, is challenging, and its link to relevant features of the underlying microstructure remain unclear (Jespersen et al, 2010; Le Bihan, 2013; Maier et al, 2010; Tietze et al, 2015; Wu and Cheung, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Tietze et al . proposed the usage of MK′ (derived from a fast kurtosis sequence) for glioma grading and demonstrated that the mean value of MK′ in the tumor core was significantly higher in HGGs than in LGGs 8 . Common outcome in the aforementioned studies is the degree of the diagnostic accuracy of DKI for the conventional glioma grading (HGG vs. LGG).…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies have investigated DKI in gliomas (grade I–IV) 17,22-25. Previous DKI studies have focused on the evaluation of differences in mean DKI parameters between low-grade gliomas (grade I–II) and high-grade gliomas (grade III–IV)22-25, while comparisons between specific grades or glioma subtypes have been limited.…”
Section: Introductionmentioning
confidence: 99%